Navigating value networks to co‐create sustainable business models: An actionable staging approach. (11th May 2022) - Pedersen, Signe; Clausen, Christian; Jørgensen, Michael Søgaard
Abstract: Sustainable transitions typically require collaboration between multiple actors in the value chain or value network. Recent research has emphasized mapping of stakeholders and values as a starting point for identifying opportunities to realign these relationships, followed by business model experimentation to enable change. However, a simple mapping exercise does not consider the interplay between actors' concerns, business models, and interpretations of sustainability. Pedersen et al. (2022) advocated that aligning concerns is essential to collaborative design and innovation, and requires continuous negotiation between multiple actors. Here, we present a microlevel in‐depth case study to examine how alignment across central value chain actors may be facilitated through the staging of numerous negotiations during the innovation process. Drawing on the staging negotiation spaces co‐design framework, we provide insight into the content of multiple negotiations concerned with different aspects of sustainability during the development of a more sustainable laundry service system on the Danish island of Bornholm. Our findings illustrate how both value chain actors and a third‐party intermediary stage negotiations, and elaborate the framework by attending to the strategic navigational efforts of network alignment through negotiations.